Sistem Informasi Pelayanan Klinik Berbasis Web (Studi Kasus: Klinik Annisa Medika 2) - Ayu Putri Hanifah; Yuli Fitrisia; Dewi Hajar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Clinic as one agency that provides health services to the general public who require the existence of an information system. In providing services and information on Clinic Annisa Medika 2 still not using a computerized system. The service is for example: patient registration is still done by the patient must come directly to the clinic, do not have queue system in treatment, some patients who want to do health consultation often experience disappointment, and medical record management which have many weaknesses such as difficulty search for files, allowing the occurrence of damage and errors of writing and reading. Therefore, built a web-based clinical information service system using laravel framework with MVC design (Model-View-Controller) that can provide information about registration of medication, queue treatment using queue with priority with priority provisions that list online, offline, and seat number. Testing the system is done by 2 ways of testing black box and statisfaction scale. From the black box test results that have been done based on 33 test items indicate that the system has been 100% successfully built in accordance with the expected. Similarly, the test results statisfaction scale by measuring the understanding how satisfied users in using software that has been made to show that the average patient satisfaction is 0.03, physician satisfaction is 0.13 and the satisfaction of the officer is 0.39 with a big value of 0, the greater the value then the qualifications assessed increasingly good.